Small Bowel Obstruction due to Anomalous Congenital Bands in Children - Basak Erginel; Feryal Gun Soysal; Huseyin Ozbey; Erbug Keskin; Alaattin Celik; Aslı Karadag; Tansu Salman (Gastroenterology Research and Practice)
Introduction. The aim of the study was to evaluate our children who are operated on for anomalous congenital band while increasing the awareness of this rare reason of intestinal obstruction in children which causes a diagnostic challenge. Patients and Methods. We retrospectively reviewed the records of fourteen children treated surgically for intestinal obstructions caused by anomalous congenital bands. Results. The bands were located between the following regions: the ascending colon and the mesentery of the terminal ileum in 4 patients, the jejunum and mesentery of the terminal ileum in 3 patients, the ileum and mesentery of the terminal ileum in 2 patients, the ligament of Treitz and mesentery of the jejunum in one patient, the ligament of Treitz and mesentery of the terminal ileum in one patient, duodenum and duodenum in one patient, the ileum and mesentery of the ileum in one patient, the jejunum and mesentery of the jejunum in one patient, and Meckel’s diverticulum and its ileal mesentery in one patient. Band excision was adequate in all of the patients except the two who received resection anastomosis for intestinal necrosis. Conclusion. Although congenital anomalous bands are rare, they should be considered in the differential diagnosis of patients with an intestinal obstruction.